Drug Delivery Systems for the Oral Administration of Antimicrobial Peptides: Promising Tools to Treat Infectious Diseases - Deshayes, Caroline; Arafath, Md. Nasir; Apaire-Marchais, Véronique; Roger, Emilie (Frontiers in Medical Technology, 2022)
Antimicrobial peptides (AMPs) have a great potential to face the global expansion of antimicrobial resistance (AMR) associated to the development of multidrug-resistant (MDR) pathogens. AMPs are usually composed of 10–50 amino acids with a broad structural diversity and present a range of antimicrobial activities. Unfortunately, even if the oral route is the most convenient one, currently approved therapeutic AMPs are mostly administrated by the intravenous route. Thus, the development of novel drug delivery systems (DDSs) represents a promising opportunity to protect AMPs from chemical and enzymatic degradation through the gastrointestinal tract and to increase intestinal permeability leading to high bioavailability. In this review, the classification and properties as well as mechanisms of the AMPs used in infectiology are first described. Then, the different pharmaceutical forms existing in the market for oral administration are presented. Finally, the formulation technologies, including microparticle- and nanoparticle-based DDSs, used to improve the oral bioavailability of AMPs are reviewed.